17.7k views
5 votes
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided

Find the inverse function for f(2)= square root of 2x - 6.

Note: Enter your answer and show all the steps that you use to solve this problem-example-1
User Jondykeman
by
5.1k points

2 Answers

7 votes

Answer:

y = ( x^2 / 2 ) + 3

Explanation:

Swap x and y, then isolate y to find a function's inverse

x = sqrt ( 2y - 6 )

x^2 = 2y - 6

x^2 + 6 = 2y

( x^2 / 2 ) + 3 = y

y = ( x^2 / 2 ) + 3 is the final answer.

User Kerox
by
5.3k points
1 vote
The roots are-4 and 7y=x² - 3x - 28The roots are
-9 and 2x² = 18 - 7xThe roots are-4,and 2y = x² + 2x -8The roots are-8 and 10x² - 2x - 6 = 74The roots are
-15 and-1x² + 15 = - 16xThe roots are-5 and 9y=x² - 4x - 45The roots are
4 and 14x² - x + 56 = 17xThe roots are
2 and 27x² - 29x = - 54
User Woodbase
by
5.3k points